1999
DOI: 10.1016/s0169-328x(99)00151-5
|View full text |Cite
|
Sign up to set email alerts
|

l-arginine uptake, the citrulline–NO cycle and arginase II in the rat brain: an in situ hybridization study

Abstract: 2Nitric oxide (NO) is synthesized from a unique precursor, arginine, by nitric oxide synthase (NOS). In brain cells, arginine is supplied by protein breakdown or extracted from the blood through cationic amino acid transporters (CATs). Arginine can also be recycled from the citrulline produced by NOS activity, through argininosuccinate synthetase (AS) and argininosuccinate lyase (AL) activities, and metabolized by arginase. NOS, AS and AL constitute the so-called citrulline-NO cycle. In order to better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 47 publications
5
78
1
1
Order By: Relevance
“…It has been reported that arginase II mRNA is present ubiquitously in nNOS-positive neurons. 21) Therefore, we presume that arginase II regulates nNOS-dependent NO production followed by neurite outgrowth in PC12h cells.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that arginase II mRNA is present ubiquitously in nNOS-positive neurons. 21) Therefore, we presume that arginase II regulates nNOS-dependent NO production followed by neurite outgrowth in PC12h cells.…”
Section: Discussionmentioning
confidence: 92%
“…32 Centrally, some studies have suggested that NO can enhance reflex bradycardia and depressor response 33,34 ; others believe that increased NO can set BP at a higher level. 35 Given that arginase II may reciprocally regulate NO bioavailability, it is also possible that a lack of arginase II may result in a central resetting of BP.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is supplied to neurones by extraction from the blood through cationic amino acid transporters and by protein breakdown. 19 Arginine is also recycled from citrulline in many tissues, including the brain, and it is this pathway that requires ASL. Arginine is the precursor to many compounds, including nitric oxide and creatine.…”
Section: Discussionmentioning
confidence: 99%